2013
DOI: 10.1158/2159-8290.cd-13-0092
|View full text |Cite
|
Sign up to set email alerts
|

Succinate Dehydrogenase Mutation Underlies Global Epigenomic Divergence in Gastrointestinal Stromal Tumor

Abstract: Gastrointestinal stromal tumors (GIST) harbor driver mutations of signal transduction kinases such as KIT, or, alternatively, manifest loss-of-function defects in the mitochondrial succinate dehydrogenase (SDH) complex, a component of the Krebs cycle and electron transport chain. We have uncovered a striking divergence between the DNA methylation profiles of SDH-deficient GIST (n = 24) versus KIT tyrosine kinase pathway–mutated GIST (n = 39). Infinium 450K methylation array analysis of formalin-fixed paraffin-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
258
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 298 publications
(281 citation statements)
references
References 28 publications
17
258
1
2
Order By: Relevance
“…59 Indeed, SDH-deficient GISTs show a global increase in DNA methylation similar to that seen in gliomas and leukemias with IDH1 and IDH2 mutations. 60 Germline mutations in SDHA, SDHB, or SDHC increase the risk not only for the development of one or more SDH-deficient GISTs but also for paragangliomas (Carney-Stratakis syndrome). 10,61 The GISTs in affected patients show either loss or somatic mutation (second hit) of the remaining wild-type allele.…”
Section: Sdh-deficient Gistsmentioning
confidence: 99%
“…59 Indeed, SDH-deficient GISTs show a global increase in DNA methylation similar to that seen in gliomas and leukemias with IDH1 and IDH2 mutations. 60 Germline mutations in SDHA, SDHB, or SDHC increase the risk not only for the development of one or more SDH-deficient GISTs but also for paragangliomas (Carney-Stratakis syndrome). 10,61 The GISTs in affected patients show either loss or somatic mutation (second hit) of the remaining wild-type allele.…”
Section: Sdh-deficient Gistsmentioning
confidence: 99%
“…Importantly, both SDH mutant PCCs/PGLs as well as GISTs have been recently shown to display a hypermethylator phenotype, exposing a vital interplay among succinate metabolism, epigenetic disruptions, and tissue-specific tumorigenesis. 37,65,80 conclusion Familial PCC/PGL syndromes were initially thought to predispose only to PCCs and PGLs, but several tumors, including GISTs, RCCs, and PAs, have expanded the SDH-associated tumor spectrum. Extensive clinical variability can be expected, even among carriers of an identical SDH germ-line mutation, with tumor phenotypes being only partially expressed, as in the Carney-Stratakis dyad.…”
Section: Mechanisms Of Biallelic Inactivationmentioning
confidence: 99%
“…28,29 In comparison to the well-established use of HM-450K assays on FF tissues and cell lines, the application of FFPE-derived DNA in HM-450K assays may be hindered due to a lack of sufficient evidence proving the feasibility and reproducibility of this approach. Few recent studies describing the performance of HM-450K assays on FFPE tissue have shown a good concordance between matched FF and FFPE tissue when applying the Illumina DNA restoration procedure on DNA from fixed tissue.…”
Section: Ffpe Tissue Epigenomics Tc De Ruijter Et Almentioning
confidence: 99%